Duration of Leave and Resident Fathers' Involvement in Infant Care in Australia - Hosking, A; Whitehouse, G; Baxter, Janeen (My University, 2010)
This article uses time-diary data from the Longitudinal Study of Australian Children (LSAC; N = 2,157 weekday diaries; N = 2,110 weekend diaries) to examine differences in infants' time with a resident father at age 4–19 months according to fathers' duration of leave around the birth. Results showed that those infants whose fathers took 4 weeks' leave or longer spent no more time with their father than did infants whose fathers took a shorter leave or no leave. We observed a positive association between any leave and sole father care on weekend days but not weekdays. The findings suggest that moderate increases in leave duration may not promote greater father involvement in Australia.
Journal of Marriage and Family
Keywords: Families -- Parents and Parenting; Families -- Fathers; Employment -- Parental leave; Families and relationships; Labour market; Families; Employment; Parents and Parenting; Parental leave; Fathers; Families and relationships; Employment and unemployment